Bulgaria Functional and Governance Analysis - World Bank (World Bank, Sofia, 2021)
Bulgaria exhibits one of the lowest innovation performances in Europe, driven by very low levels of research investment compared to peers. This slow growth will likely be exacerbated by the Coronavirus (COVID-19) pandemic and ensuing economic crisis, which have disproportionately affected Bulgaria’s smaller and younger firms, a typically the firms with the highest potential for productivity growth. Moreover, a rapidly aging population and high emigration rates raise the potential for increasing labor shortages and skills mismatches over the medium term. Accelerating productivity growth will require large improvements to the country’s science, technology, and innovation (STI) performance, which currently ranks among the weakest in the EU across multiple indicators. There is a clear need to modernize the national research system particularly in the public sector to improve the performance of research institutions, with a focus on research excellence, market-oriented research agendas, and technology transfer. The goal of this report is to provide in-depth assessments of the functionality and governance of key Bulgarian STI support instruments and to provide recommendations for improvement of the government’s current and future portfolio of STI support programs. The work represents the second phase of the World Bank’s Bulgaria Public Expenditure Review for Science, Technology, and Innovation (PER STI) project.